Partner market opportunities and relationship stability - Rapp, Ingmar; Klein, Thomas; Fronk, Sebastian; Stauder, Johannes (Comparative population studies, 2015)
Abstract : Although partner market opportunities are generally considered to be important for relationship stability, they have never been measured accurately. In order to be able to test the anticipated effects of partner market opportunities, this study conceptualises them as individual opportunities for contact and interaction in concrete social contexts, like the neighbourhood, the workplace, leisure activities, etc. Using data from the German Marriage Market Survey, we first examine the impact of individual partner market opportunities on the risk of separation. Second, we examine to what extend the most frequently studied determinants of divorce and separation depend on partner market opportunities. Our results show that the number of opposite sex contacts increases the probability of separation. Sharing the same contacts with one’s partner decreases the risk of separation. Our results indicate further that reducing opposite sex contacts in the course of the relationship is partly responsible for the higher stability of longer-lasting relationships. Having a migration background is associated with fewer opposite sex contacts. This means that having a migration background would be more destabilising if these individuals did not have less opposite sex contacts than individuals without a migration background. In contrast, joint home ownership, church attendance, higher education and residing in western Germany would generally be more stabilising if these factors were not connected with more opposite sex contacts.